2022
DOI: 10.1101/2022.10.17.512591
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MYT1L is required for suppressing earlier neuronal development programs in the adult mouse brain

Abstract: In vitro studies indicate the neurodevelopmental disorder gene Myelin Transcription Factor 1 Like (MYT1L) suppresses non-neuronal lineage genes during fibroblast-to-neuron direct differentiation. However, MYT1L's molecular and cellular functions during differentiation in the mammalian brain have not been fully characterized. Here, we found that MYT1L loss leads to up-regulated deep layer (DL) but down-regulated upper layer (UL) neuron gene expression, corresponding to an increased ratio of DL/UL neurons in mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…In contrast to our study, Chen et al report an increased Q fraction and a decrease in SOX2+ neural stem cells in Myt1l-deficient mice at E14.5 and suggested MYT1L mainly acts as a transcriptional activator. However, in a recent preprint the same authors found that MYT1L bound and repressed promoters and enhancers of genes involved in early neuronal development programs [71]. Here, using single cell transcriptomics, we show that MYT1L-bound genes are indeed activated in cortical neurons upon loss of MYT1L, supporting its role as a repressor.…”
Section: Discussionsupporting
confidence: 54%
“…In contrast to our study, Chen et al report an increased Q fraction and a decrease in SOX2+ neural stem cells in Myt1l-deficient mice at E14.5 and suggested MYT1L mainly acts as a transcriptional activator. However, in a recent preprint the same authors found that MYT1L bound and repressed promoters and enhancers of genes involved in early neuronal development programs [71]. Here, using single cell transcriptomics, we show that MYT1L-bound genes are indeed activated in cortical neurons upon loss of MYT1L, supporting its role as a repressor.…”
Section: Discussionsupporting
confidence: 54%
“…MYT1L also represses deeper layer neuron transcriptional program in the adult prefrontal cortex (45) and non-neuronal genes (44,46). SIN3-HDAC is a major corepressor that achieves MYT-mediated transcriptional suppression in vertebrates (45,47).…”
Section: Discussionmentioning
confidence: 99%
“…Both MYT1 and MYT1L bind to a consensus DNA motif AAAGTTT (25) and transcriptionally suppress the Notch signaling pathway, which negatively regulates neurogenesis and, in turn, promotes neurogenesis (43, 44). MYT1L also represses deeper layer neuron transcriptional program in the adult prefrontal cortex (45) and non-neuronal genes (44, 46). SIN3-HDAC is a major corepressor that achieves MYT-mediated transcriptional suppression in vertebrates (45, 47).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation